2021
DOI: 10.1093/sleep/zsab192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of upper airway fat on tongue dilation during inspiration in awake people with obstructive sleep apnea

Abstract: Study Objectives To investigate the effect of upper airway fat composition on tongue inspiratory movement and obstructive sleep apnea (OSA). Methods Participants without or with untreated OSA underwent a 3T magnetic resonance imaging (MRI) scan. Anatomical measurements were obtained from T2-weighted images. Mid-sagittal inspiratory tongue movements were imaged using tagged MRI during wakefulness. Tissue volumes and percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Compared to other somatic muscles, AT accumulation in the tongue showed a higher correlation with BMI and therefore, with obesity severity, which is strongly correlated with OSA severity [ 48 ]. Jugé et al found similar results, and observed a significant positive correlation between tongue AT and BMI and older ages [ 49 ]. Our results showed that tongue fat% did not significantly differ between OSA categories and the control group, but the midsagittal region fat% parameter did.…”
Section: Discussionmentioning
confidence: 56%
“…Compared to other somatic muscles, AT accumulation in the tongue showed a higher correlation with BMI and therefore, with obesity severity, which is strongly correlated with OSA severity [ 48 ]. Jugé et al found similar results, and observed a significant positive correlation between tongue AT and BMI and older ages [ 49 ]. Our results showed that tongue fat% did not significantly differ between OSA categories and the control group, but the midsagittal region fat% parameter did.…”
Section: Discussionmentioning
confidence: 56%
“…Patients with CHF often present with obstructive sleep apnea syndrome (OSAS) [54]. We know that one of the main causes of OSAS is morphological and functional alterations of the tongue, in particular, an increase in posterior volume and an alteration of the intervention of the autonomic nervous system [55,56]. Lingual dysfunction in CHF and OSAS raises the likelihood of systemic metabolic disorders, with the risk of further cardiovascular sequelae, the onset of metabolic syndrome, and cognitive impairment [56].…”
Section: Mri: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This technique has been widely used to assess the fat content in the liver. 1,2 In the past decade, there has been increased interest in MRI quantification of the fat fraction (FF) of the tongue and airway muscles, [3][4][5][6][7] because these FFs may help to elucidate the mechanisms of obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%
“…No significant differences were found between the FFs in the patients with OSA and controls. 3 To understand and clarify the conflicting observations, we will examine the FF estimation methods used in the earlier studies and seek a more accurate method to measure FFs.…”
mentioning
confidence: 99%
See 1 more Smart Citation